Implications of Unregistered Polygamous Marriages For Children's Rights in Indonesia - Mutarofik, Mutarofik; Trigiyatno, Ali; Arifin, Ihyaul; Achmad, Musyafa; Azizah, Antik (TAQNIN: Jurnal Syariah dan Hukum, 2024)
Polygamous marriages have become the latest issue regarding complaints about the impact of the practice of polygamy, where many husbands remarry without their wives' permission, some even do it secretly. Polygamy is still a debate in society. As a solution, some couples choose to carry out "underhand" marriages which are not legally valid and have no legal force. Therefore, the author wants to examine the impact of unregistered polygamous marriages on children's rights. So, the aim of this research is to determine the implications of unregistered polygamous marriages on children's rights. This research method uses qualitative techniques with a normative approach. The results of this research include that unregistered polygamous marriages have an impact on children's rights because the state cannot protect the rights of unregistered children.